ENGAGING STRATEGIES FOR TEACHING ENGLISH THROUGH COLLABORATION TECHNIQUE - Cut Mawar Helmanda; Siti Safura (Prologue: Journal on Language and Literature, 2024)
The objectives of this study were two points: first, to examine the implementation of collaboration techniques, and second, to assess students’ perspective to these techniques. The study focused on the students in the English department at the University of Muhammadiyah Aceh, with the sample consist-ing of students from the academic year 2021, 2022, and 2023, selected through random sampling. Data collection employed observation and interviews as instruments, with 15 students participating in the interview process. The observation results highlighted the prevalence of collaboration activities and think-pair-share as opposed to other techniques in classroom settings. Furthermore, students’ responses to the implementation of collaboration technique were predominantly positive. Notably, students expressed increased student engagement, enhanced communication abilities, a diversity of viewpoints, peer learning, critical thinking, and the acquisition of crucial life skills.